Training Administrative Staff to Become Key Players in the Internationalization of Higher Education - Hunter, Fiona (International Higher Education, 2018)
A recent survey has sought to understand the current and potential roles that administrative staff might play in internationalization and to identify relevant training provision that could enable them to become more active in, and committed to, the internationalization strategies of their institutions. It reveals that there is still much that needs to be done and that the learning needs to take place both at individual and institutional levels.